2020
DOI: 10.1021/acs.est.0c06357
|View full text |Cite
|
Sign up to set email alerts
|

Flushing of Stagnant Premise Water Systems after the COVID-19 Shutdown Can Reduce Infection Risk by Legionella and Mycobacterium spp.

Abstract: There is concern about potential exposure to opportunistic pathogens when reopening buildings closed due to the COVID-19 pandemic. In this study, water samples were collected before, during, and after flushing showers in five unoccupied (i.e., for ∼2 months) university buildings with quantification of opportunists via a cultivation-based assay (Legionella pneumophila only) and quantitative PCR. L. pneumophila were not detected by either method; Legionella spp., nontuberculous mycobacteria (NTM), and Mycobacter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
100
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(112 citation statements)
references
References 46 publications
12
100
0
Order By: Relevance
“…These are all critical aspects related to Legionella persistence in man-made systems that contribute to a higher or lower legionellosis risk. The studies considered in Table 1 cover different water settings, including cooling towers [55][56][57], premise plumbing from hospitals [51,52,54,[58][59][60][61][62][63][64] and hotels [45,48,[64][65][66][67][68][69], residential potable water systems [46,70,71], and other facilities [72][73][74][75][76][77][78].…”
Section: Main Research Topicsmentioning
confidence: 99%
See 2 more Smart Citations
“…These are all critical aspects related to Legionella persistence in man-made systems that contribute to a higher or lower legionellosis risk. The studies considered in Table 1 cover different water settings, including cooling towers [55][56][57], premise plumbing from hospitals [51,52,54,[58][59][60][61][62][63][64] and hotels [45,48,[64][65][66][67][68][69], residential potable water systems [46,70,71], and other facilities [72][73][74][75][76][77][78].…”
Section: Main Research Topicsmentioning
confidence: 99%
“…Chemical Disinfection Programs shape bacterial communities and reduce Legionella positivities (chlorination, chloramine, chlorine dioxide, copper-silver ionization, hydrogen peroxide and silver salts, NEOW) [51,52,54,56,61,62,66,72,73,[79][80][81] Effective temperature control reduces Legionella incidence [60,70,82] Water stagnation vs. water flushing [48,59,65,71,78,83]…”
Section: Microbial Control Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the potential limitations in this study was to find Legionella free premises and buildings, because generally man-made water systems were colonized by Legionella. Hozalski et al (2020) reported that flushing stagnant network water systems after the COVID-19 shutdown can reduce Legionella infection risk. The same study suggested that flushing could rapidly improve water quality in restricted buildings, but the improvement may only last a few days.…”
Section: Resultsmentioning
confidence: 99%
“…These include well designed hospital water systems, and maintenance of hot water systems, to ensure inhibitory temperatures are maintained. Hot water pipes need to be properly insulated to prevent the warming of adjacent cold-water pipes, stagnation sites such as blind pipe sections and holding tanks eliminated, and material that supports legionella growth minimised [139][140][141][142]. A metanalysis has shown that temperatures of 55-59 • C are associated with a low probability of Legionella species being detectable in water samples, and in cold water kept below 20 • C [143,144].…”
Section: Prevention and Public Healthmentioning
confidence: 99%